A promising self-nanoemulsifying adjuvant with plant-derived saponin D boosts immune response and exerts an anti-tumor effect - Luo, Xing; Song, Zhen; Zeng, Xiaogqiang; Ye, Yan; Zheng, Hailin; Cai, Dingyi; Yuan, Qingpeng; Li, Haibo; Tong, Yanan; Lu, Dongshui; Liu, Yuheng; Zeng, Hao; et al. (Frontiers in Immunology, 2023)
Low immunogenicity of the tumor antigen and unacceptable toxicity of adjuvants had hindered the application and development of the tumor vaccine. Hence, we designed a novel anti-tumor vaccine composed by the plant immunostimulant molecular nanoadjuvant (SND) and antigen OVA to reinvigorate immune response and inhibit tumor progression. We found that the nanoadjuvant had good characteristics including the average particle size of 26.35 ± 0.225 nm, narrow distribution of 0.221 ± 1.76, and stability zeta potential of -12.9 ± 0.83 mV. And also, the SND nanoadjuvant had good stability (size, PDI, zeta potential, antigen stability) and low toxicity in vitro and in vivo, and delayed antigen release in vivo. We found that the humoral immune response (IgG, IgG1, IgG2a, and IgG2b) and cellular immune level (cytokines of splenocytes including IFN-γ, IL-4, IL-1β and IL-17A) were both improved greatly after injected immunization at 0, 14, 28 days with the novel nanoadjuvant and antigen OVA. Importantly, this novel nanoadjuvant combined with OVA might lead to the induction of the prevent and treatment efficacy in the E.G7-OVA tumor-bearing mice. These results suggested that the novel nanoadjuvant encapsulated natural plant immunostimulant molecular be a good candidate of tumor vaccine adjuvant for reinvigorating the immune response and powerfully inhibiting tumor growth effect.